Analisis Pasar Monopoli Dalam Perspektif Ekonomi ISlam Dan Etika Bisnis Islam - Nia Pususpita Hapsari; Endang Ruswanti (Jurnal Manajemen DIVERSIFIKASI, 2024)
Monopoly market share, namely: the composition of market share indicates that one seller orproducer dominates the market, so that it has is a market structure characterized by oneseller or producer dominating the market so that it has the power to determine prices andsupply. In an Islamic economic perspective, monopoly practices are often consideredunethical because they have the potential to harm consumers and create injustice due to thedistribution of resources. This article aims to analyze monopolized markets from theperspective of Islamic economics and Islamic business ethics by highlighting relevant Islamicbusiness ethics doctrines, such as justice, balance (mizan), and the prohibition of exploitation(gharar, and ikhtiar). Analyzing monopoly markets from the perspective of Islamic economicsand Islamic business ethics, taking into account the basic doctrines in fiqh muamalah,justice, and social responsibility. This article also discusses the implications of thesedoctrines for regulation and business practices in monopoly markets. How reviewingmonopolistic practices is contrary to the doctrine of Islamic business ethics, whichemphasizes honesty, transparency, and mutual prosperity. Research with a qualitativeapproach by analyzing literature and theories of Islamic economics and business ethics. Thisresearch concludes that monopoly markets conflict with the basic guidelines of Islamiceconomics that focus on the balanced welfare of the people. In Islamic business ethics, monopoly is considered a practice that inconsistent with the teachings of beliefs thatencourage healthy competitions and honnest trade.